Efektivitas Bauran Pemasaran Dalam Mempengaruhi Pengambilan Keputusan Konsumen Pengguna Jasa Pembiayaan - Rizki Aprilia Dwi Susanti (BIP's JURNAL BISNIS PERSPEKTIF, 2016)
The purpose of this study was to determine: the condition of the marketing mix and the behavior of consumers in making purchasing decisions, the influence of marketing mix (X) either partially or simultaneously to the behavior of consumers in making purchasing decisions (Y), and to know the marketing mix elements that most influence behavior consumers in making purchasing decisions. The independent variables in this study is product (X1), price (X2), place (X3), promotion (X4), people (X5), process (X6) and phyisical evidence (X7) and the dependent variable is the behaviour of consumers in making purchasing decision (Y). This study is classified into a descriptive correlational study. Data collection techniques in this study using questionnaires, interviews, literature review and documentation. The results of this research are: (1) There is no significant positive impact product, location and promotion on consumer behavior in the decision to use the financing services of Summit Oto Finance Branch Pamekasan.(2) There is a significant positive effect the price, people, process and physical evidence on consumer behavior in the decision to use the financing services of Summit Oto Finance Branch Pamekasan. (3) Together product, price, location, promotion, people, process and physical evidence influence consumer behavior in the decision to use the financing services of Summit Oto Finance Branch Pamekasan amounted to 65.1%, while the remaining 34.9% is influenced by other factors outside 7 these factors.